PENGETAHUAN IBU TENTANG PERMAINAN EDUKATIF UNTUK MERANGSANG PERKEMBANGAN MOTORIK PADA BALITA DI KELURAHAN UJUNG PADANG KECAMATAN PADANGSIDIMPUAN SELATAN TAHUN 2019 - ELVI SURYANI (JURNAL ILMIAH SIMANTEK, 2021)
Educative games stimulate fine motor and rough child, fine motor obtained when the child pick up the toy, fingered, holdingwith his fifth finger, and sebanya. While rough motor stimulation gained the child while manggerak-move his toys, throwing,lifting, and so forth. The purpose of this study is to know the description of knowledge of mothers who have children underfive about educational games to stimulate motor development in toddlers in Ujung Padang Urban District PadangsidimpuanSelatan Year 2019. This research is descriptive by using primary data obtained through questionnaire, where the sample of39 respondents is 25% of random sampling, which is studied by age, education, source of information, income. The result ofthe study of 39 respondents majority of knowledge less as much as 23 respondents (58.97%), based on age majority ofknowledge less 14 respondents at age 20-35 years, based on education majority of knowledge less on medium educationcounted 13 respondents (33.33%), less knowledgeable with electronic media information source as much as 13 respondents(33.33%). It is suggested that mothers with toddlers can further improve and increase knowledge about educational gamesto stimulate motor development.